Co‐Anchoring of Engineered Immunogen and Immunostimulatory Cytokines to Alum Promotes Enhanced‐Humoral Immunity (Adv. Therap. 7/2022). Issue 7 (18th July 2022) - Chang, Jason Y. H.; Agarwal, Yash; Rodrigues, Kristen A.; Momin, Noor; Ni, Kaiyuan; Read, Benjamin J.; Moyer, Tyson J.; Mehta, Naveen K.; Silva, Murillo; Suh, Heikyung; Melo, Mariane B.; Wittrup, K. Dane; et al.
Abstract : Targeted delivery of subunit protein vaccines to the draining lymph nodes by utilizing the adjuvant alum to anchor both the antigen and immunostimulatory cytokine IL‐21 to promote the overall humoral response of the vaccines. Here, IL‐21 acts as a molecular adjuvant to enhance the antibody response against the target antigen. This is reported by Darrell J. Irvine and co‐workers in article number 2100235 .